2003
DOI: 10.1002/ana.10680
|View full text |Cite
|
Sign up to set email alerts
|

Caspase activation in the limbic cortex of subjects with early Alzheimer's disease

Abstract: We investigated the cleavage of caspase-3, a marker of apoptosis, in the medial temporal lobe of older subjects with minimal cognitive deficits and low CERAD/intermediate Braak scores, that is, clinicopathological descriptors of early Alzheimer's disease (AD). The activation of caspase-3 was studied with immunoprecipitation-mass spectroscopy and immunocytochemistry, including colocalization with paired helical filaments in the neuropil and perikarya. We found that caspase-3 is activated in the parahippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 22 publications
0
58
1
1
Order By: Relevance
“…These enzymes can be broadly divided into initiator and executioner caspases, with the former functioning to initiate apoptosis by activating executioner caspases and the latter acting on downstream effector substrates that result in the progression of apoptosis and the appearance of hallmark morphological changes such as cell shrinkage, nuclear fragmentation, and membrane blebbing (19). Increasing evidence suggests that caspases are activated in the AD brain (20)(21)(22)(23)(24)(25)(26). Furthermore, components of the neuronal cytoskeleton, including tau, are targeted by caspases following apoptotic stimuli (23,(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes can be broadly divided into initiator and executioner caspases, with the former functioning to initiate apoptosis by activating executioner caspases and the latter acting on downstream effector substrates that result in the progression of apoptosis and the appearance of hallmark morphological changes such as cell shrinkage, nuclear fragmentation, and membrane blebbing (19). Increasing evidence suggests that caspases are activated in the AD brain (20)(21)(22)(23)(24)(25)(26). Furthermore, components of the neuronal cytoskeleton, including tau, are targeted by caspases following apoptotic stimuli (23,(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is a genetically programmed cell death pathway that typically involves caspase activation and distinct morphological changes in the cell. Neurons exhibiting apoptotic features have been observed in postmortem tissue of individuals affected by stroke and from patients diagnosed with Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis (ALS) (Tatton et al, 1998;Martin, 1999;Gastard et al, 2003;Chan, 2004). Furthermore, a number of studies have demonstrated that molecular and pharmacological inhibitors of caspases can reduce or delay neuronal cell death in animal models of cerebral ischemia and neurodegenerative disease (Li, 2000;Le et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, activation of caspase 3 was found to occur in the parahippocampal gyrus in brains from patients with mild forms of Alzheimer's disease. Caspase 3 immunoreactivity was also co-localized with paired helical filaments in neurons, suggesting that caspase 3 activation may contribute to the formation of neurofibrillary tangles [79]. This premise was further supported by a study that demonstrated the existence of fodrin caspase-cleavage product in the hippocampus of Alzheimer's patients, which was co-localized with neurofibrillary tangles [190].…”
Section: Onset Of Apoptotic Injury By Caspases and Their Association mentioning
confidence: 76%